2021
DOI: 10.3389/fcell.2021.681123
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic Crossover Patterning

Abstract: Proper number and placement of meiotic crossovers is vital to chromosome segregation, with failures in normal crossover distribution often resulting in aneuploidy and infertility. Meiotic crossovers are formed via homologous repair of programmed double-strand breaks (DSBs). Although DSBs occur throughout the genome, crossover placement is intricately patterned, as observed first in early genetic studies by Muller and Sturtevant. Three types of patterning events have been identified. Interference, first describ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 204 publications
(263 reference statements)
3
48
0
Order By: Relevance
“…We showed that, for most species, the smallest chromosome had roughly one or two COs, independently of chromosome size. This is in agreement with the idea that CO assurance is a ubiquitous regulation process among angiosperms (Pazhayam et al, 2021). Moreover, it seems that this constraint imposes a kind of basal recombination rate for each species, on the order of 50/ Sc cM/Mb, where Sc is the size of the lowest chromosome in Mb.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…We showed that, for most species, the smallest chromosome had roughly one or two COs, independently of chromosome size. This is in agreement with the idea that CO assurance is a ubiquitous regulation process among angiosperms (Pazhayam et al, 2021). Moreover, it seems that this constraint imposes a kind of basal recombination rate for each species, on the order of 50/ Sc cM/Mb, where Sc is the size of the lowest chromosome in Mb.…”
Section: Discussionsupporting
confidence: 93%
“…Recombination also plays an evolutionary role by breaking the linkage between neighbouring sites and creating new genetic combinations transmitted to the next generation upon which selection can act (Barton, 1995; Charlesworth and Jensen, 2021; Otto, 2009). However, the number and location of crossovers (COs) along the chromosome are finely regulated through mechanisms of crossover assurance, interference and homeostasis (Otto and Payseur, 2019; Pazhayam et al, 2021). In most species, at least one CO per chromosome is mandatory to achieve proper segregation and to avoid deleterious consequences of nondisjunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the SC in crossover interference A variety of physical and mathematical models have been proposed to explain crossover interference (reviewed by Otto and Payseur, 2019;Pazhayam et al, 2021). An early model suggested that the SC might behave as a "compartment" within which recombination proteins might diffuse and accumulate cooperatively at a limited number of recombination sites (Holliday, Robin, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are exceptions (reviewed in [ 6 ]), COs are essential for accurate chromosome segregation in most organisms. Specifically, COs in conjunction with sister chromatid cohesion (SCC) result in structures referred to as “chiasmata”, which tether homolog pairs, thereby facilitating their correct orientation on the MI spindle [ 7 , 8 , 9 ].…”
Section: Crossover Formation Triggers Chromosome Remodeling In Late P...mentioning
confidence: 99%